Poor Officiatintg, Lack of Sportsmanship Spirit and Poor Facilities as Triggers of Violence Among Sports Audience in Portharcourt Metropolis, Nigeria - Olumide Olusoga Ezomoh; Gloria O. Nwankwo (Borong Newinera Publisher, 2022)
This study examined if poor officiating, lack of sportsmanship spirit and poor facilities are triggers of violence among sports audience in Port Harcourt Metropolis, Nigeria. This study was conducted among the inhabitants of Port Harcourt metropolis in River state. The descriptive survey research design and a sample size of 1,000 participants were used. The multi-stage sampling technique, a structured, validated and modified Likert type questionnaire were employed. The reliability of the instrument was determined through the Crombach Alpha, which gave a value of r = 0.89. The data collected was analyzed using the Chi-square statistics. The study revealed that poor officiating, lack of Spirit of Sportsmanship and poor facility were triggers of violence among sports audience in Port Harcourt metropolis, Nigeria. It was consequently recommended that only competent and knowledgeable officials should be used for matches. Both players and supporters should be educated on the rules of games and trained to accept the decision of referees’ umpires etc. and should not see competition as a do-or-die affair/event.